Reliability Assessment of Bridge Decks: A Case Study of Three Bridges Along Lagos – Ibadan Expressway. (2012)
The ageing and gradual deterioration of bridges in Nigeria needs balancing of cost-effective plans for bridge maintenance, rehabilitation and replacement. This research aims at assessing the reliability of bridges using three existing highway bridges along Lagos-Ibadan expressway as a case study. Visual inspection, sounding, half-cell potential and chloride concentration tests were utilized to evaluate the conditions of the bridges. Deteriorations were observed on the decks’ surfaces. The level of corrosion on one deck was active and uncertain in the remaining two. The chloride concentrations on all the decks were within AASHTO standards and only one of the decks had delaminated. The results revealed that none of the decks needs total replacement but all require some form of rehabilitation.